Magnetization and 57Fe hyperfine fields in Y2Fe17Z3-??(Z=H, C, or N) interstitial compounds - COEY, JOHN MICHAEL DAVID (American Physical Society, 1992)
Measured magnetization and 57Fe hyperfine fields at T?_0 K for Y2Fe17 and Y2Fe17Z3-??, with Z=H, C, or N and ???_0.5, are analyzed to determine the influence of the interstitial atoms on the 3d magnetism. All are weak ferromagnets with a nearly-full 3d subband, although when Z=N, the magnetic moment of 38.1?_B is very close to the fully saturated value of 39.4?_B. On a local scale, the order of hyperfine fields Bhf4f(=35 T)>Bhf6g (=33 T)>Bhf12j (=30 T)>Bhf12k (=28 T) is different from that of the local magnetic moments given by several recent band calculations for Y2Fe17, ?_4f (=2.5?_B)>?_12j (=2.2?_B)>?_12k (=2.0?_B)>?_6g (=1.9 ?_B), reflecting a large 4s-transferred hyperfine field at 6g sites which have very short Fe-Fe distances. The volume of samples with Z=C and N are identical, and so the chemical effects of the interstitials can be distinguished; both the local magnetic moment and hyperfine fields are systematically smaller in the carbide than the nitride by 5% and 12%, respectively.
PUBLISHED
Keywords: Physics